Proof-of-Concept Integration of Heterogeneous Biobank IT Infrastructures into a Hybrid Biobanking Network - Mate, Sebastian; Kadioglu, Dennis; Majeed, Raphael W; Stöhr, Mark R; Folz, Michael; Vormstein, Patric; Storf, Holger; Brucker, Daniel P; Keune, Dietmar; Zerbe, Norman; Hummel, Michael; Senghas, Karsten; et al. (Studies in health technology and informatics, 2017)
Cross-institutional biobank networks hold the promise of supporting medicine by enabling the exchange of associated samples for research purposes. Various initiatives, such as BBMRI-ERIC and German Biobank Node (GBN), aim to interconnect biobanks for enabling the compilation of joint biomaterial collections. However, building software platforms to facilitate such collaboration is challenging due to the heterogeneity of existing biobank IT infrastructures and the necessary efforts for installing and maintaining additional software components. As a remedy, this paper presents the concept of a hybrid network for interconnecting already existing software components commonly found in biobanks and a proof-of-concept implementation of two prototypes involving four biobanks of the German Biobank Node. Here we demonstrate the successful bridging of two IT systems found in many German biobanks - Samply and i2b2.
EVALuna2:189